2016
DOI: 10.3390/membranes6030040
|View full text |Cite
|
Sign up to set email alerts
|

Permeability-Selectivity Analysis of Microfiltration and Ultrafiltration Membranes: Effect of Pore Size and Shape Distribution and Membrane Stretching

Abstract: We present a modeling approach to determine the permeability-selectivity tradeoff for microfiltration and ultrafiltration membranes with a distribution of pore sizes and pore shapes. Using the formulated permeability-selectivity model, the effect of pore aspect ratio and pore size distribution on the permeability-selectivity tradeoff of the membrane is analyzed. A finite element model is developed to study the effect of membrane stretching on the distribution of pore sizes and shapes in the stretched membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 14 publications
1
32
0
2
Order By: Relevance
“…Further, the increase of working pressure increased the retentate temperature and permeate flux ( Figure 2 ). Higher temperatures resulted in lower viscosity of the feed, that leads to higher permeate flux [ 18 , 29 ]. The highest average permeate flux during nanofiltration (39.45 L/m 2 h) and reverse osmosis process (17.75 L/m 2 h) was measured at 5.5 MPa without cooling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the increase of working pressure increased the retentate temperature and permeate flux ( Figure 2 ). Higher temperatures resulted in lower viscosity of the feed, that leads to higher permeate flux [ 18 , 29 ]. The highest average permeate flux during nanofiltration (39.45 L/m 2 h) and reverse osmosis process (17.75 L/m 2 h) was measured at 5.5 MPa without cooling.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the increase of working pressure increased the retentate temperature and permeate flux ( Figure 2). Higher temperatures resulted in lower viscosity of the feed, that leads to higher permeate flux [18,29]…”
Section: Processing Parametersmentioning
confidence: 99%
“…2(e). 50 This indicates that the presence of ND and ceria nanoparticles could create additional pathways for water flow, without increasing the pore size. The enhanced surface roughness (Fig.…”
Section: Studies On Mechanical Properties Of the Membranesmentioning
confidence: 99%
“…However, a measurement on CG scaffolds demonstrates well expected result where cell migration increases with increasing pore size [ 77 ]. Also, a study of stretched porous membranes [ 78 ] showed a positive shift in the mean pore size and permeability that accompanies membrane stretching.…”
Section: In Silico Modelmentioning
confidence: 99%